Demography of the Intertidal Fucoid Hormosira banksii: Importance of Recruitment to Local Abundance. Issue 2 (3rd March 2021) - Lewis, Ryan D.; Johnson, Craig R.; Wright, Jeffrey T.
Abstract : Canopy‐forming macroalgae form the basis of diverse coastal ecosystems globally. The fucoid Hormosira banksii is often the dominant canopy‐forming macroalga in the temperate intertidal of southern Australia and New Zealand, where it is commonly associated with an understory of coralline turf. Hormosira banksii is susceptible to both natural and anthropogenic disturbance and despite its abundance, few studies have examined the demography of this important species. This study determined the demographic response of H. banksii to different gradients of disturbance to both its canopy and to the understory coralline turf. We established plots in which the density of H. banksii and/or understory coralline turf was manipulated in a pulse perturbation to simulate a disturbance event. The manipulated plots contained eight treatments ranging from 100% removal of H. banksii to 100% removal of the understory coralline turf. We then measured recruitment and followed individual recruits for up to 18 months to determine growth and survivorship. We found that H. banksii recruitment was seasonally variable throughout the experiment and highest over summer, survivorship of recruits was generally high, and the species was slow‐growing and long‐lived. Moreover, the level of disturbance did not seem to affect recruitment, growth, or survivorship and post‐recruitment mortality was independent of H. banksii density. In this system, it appears that H. banksii is a relatively long‐lived perennial species whose demography is density‐independent which appears to allow recovery from disturbance.